2015
DOI: 10.1517/17425255.2015.1075003
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of clozapine treatment response and side-effects in schizophrenia: an update

Abstract: Pharmacogenetics is a promising avenue for individualized medication of CLZ in SCZ, with several consistently replicated gene variants predicting CLZ response and side-effects. However, a large proportion of studies have yielded mixed results. Large-scale Genome-wide association studies (e.g., CRESTAR) and targeted gene studies with standardized designs (response measurements, treatment durations, plasma level monitoring) are required for further progress toward clinical translation. Additionally, in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 99 publications
0
26
0
2
Order By: Relevance
“…Several serotonergic receptor type 2A ( 5-HT2A ) gene polymorphisms have been associated with response to clozapine,34 although these associations have not been universally replicated 27,35. Studies have demonstrated an association between clozapine efficacy and genetic variants in the serotonin receptor type 2A ( 5-HT2A ),34 type 2C ( 5-HT2C ),36 and type 6 ( 5-HT6 )37 and serotonin transporter ( 5-HTT ) genes,36 although these findings have not been consistently replicated 2628.…”
Section: Pharmacogenomics and Clozapine Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Several serotonergic receptor type 2A ( 5-HT2A ) gene polymorphisms have been associated with response to clozapine,34 although these associations have not been universally replicated 27,35. Studies have demonstrated an association between clozapine efficacy and genetic variants in the serotonin receptor type 2A ( 5-HT2A ),34 type 2C ( 5-HT2C ),36 and type 6 ( 5-HT6 )37 and serotonin transporter ( 5-HTT ) genes,36 although these findings have not been consistently replicated 2628.…”
Section: Pharmacogenomics and Clozapine Responsementioning
confidence: 99%
“…Meta-analysis has confirmed the need for replication studies of much larger sample sizes to detect real associations 25,27. Most pharmacogenomic studies in clozapine use have focused on candidate genes coding for specific enzymes believed to be involved in the absorption, distribution, metabolism, and/or excretion of antipsychotic medications 27,28,89.…”
Section: Challenges In Applying Pharmacogenomics In Trs and Future DImentioning
confidence: 99%
“…To date, pharmacogenetic research has emphasized the major neurotransmitter systems involved in the pharmacodynamics and pharmacokinetics of antipsychotics. While issues with consistency exist in the findings [67][68][69][70], many of these associations could still be important. Several reasons may underlie the inconsistent results, such as different duration of clozapine treatment among the studies, different inclusion criteria for clozapine responders [23], and different ethnicities [71][72][73][74].…”
Section: Pharmacogeneticsmentioning
confidence: 99%
“…Paradoxically, GWAS of drug response, including adverse reactions to a drug, composes less than 10% of the total number of published GWAS reports and has achieved genome-wide significant association with less than 300 SNPs, averaging 2 or less per study [47,48] . Despite this limitation, these studies have still provided valuable information on the mechanisms underlying drug distribution, efficacy and toxicology [49][50][51] . For example, hepatic CYP2C19 enzyme, a CYP450 superfamily member, regulates the metabolism of many drugs, including antidepressants [52,53] , and their genetic variants were detected to have a significant effect on the choice of appropriate types and doses of clinical anticoagulants.…”
Section: Perspective On the Application Of Full Genetic Model Gwas Tomentioning
confidence: 99%